Investor aspirations for Indigenous land and sea management in Australia. Issue 2 (3rd April 2019) - Austin, B. J.; Robinson, C. J.; Tofa, M.; Garnett, S. T.
ABSTRACT: Partnerships between Indigenous peoples and non-local investors have been the source of significant innovation in environmental management across the globe. Indigenous land and sea management in Australia is a growing economic sector that has been used to create jobs, training and income in remote Indigenous Australia. While the aspirations of Indigenous people for Indigenous land and sea management have been reported widely, the aspirations of non-local investors are less clear. In this article, we present an analysis of the aspirations of investors and, in so doing, seek to strengthen partnerships between Indigenous peoples and investors globally. There can be an implicit assumption that investment in the sector is purely to achieve biophysical outcomes, such as increased protection of biodiversity in key bioregions. Our analysis suggests that this is partly true, though significantly underestimates the willingness of investors to contribute to the realisation of social, economic and cultural benefits. Based on these results, we offer two recommendations for advancing Indigenous land and sea manager-investor partnerships: (1) investors should identify and clearly communicate their aspirations for entering partnerships, and (2) Indigenous peoples should be supported to develop clear protocols for investment in their land sea management programmes.